2020
DOI: 10.1101/2020.03.28.013177
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Secreted TAL effectors protect symbiotic bacteria from entrapment within fungal hyphae

Abstract: The association of the agriculturally significant phytopathogenic fungus Rhizopus microsporus with the bacterial endosymbiont Burkholderia rhizoxinica is a remarkable example of bacteria controlling host physiology and reproduction. Here, we show that a group of transcription activator-like effectors (TALEs) called Burkholderia TALE-like proteins (BATs) from B. rhizoxinica are essential for the establishment of the symbiosis. Mutants lacking BAT proteins are unable to induce host sporulation. Utilising novel m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Holrhizin A exhibited biosurfactant activity, altered biofilm formation and cell motility to promote colonization [ 25 ]. Work pioneered by several research groups has discovered the involvement of effectors-Type III secretion system (T3SS) [ 26 ], transcription activator-like (TAL) effector [ 27 , 28 ], and Type II secretion system (T2SS) [ 23 ]. Receptors that interact with these effectors and the downstream signaling pathways eliciting specific responses remain to be identified.…”
Section: Bacterial-fungal Physical Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Holrhizin A exhibited biosurfactant activity, altered biofilm formation and cell motility to promote colonization [ 25 ]. Work pioneered by several research groups has discovered the involvement of effectors-Type III secretion system (T3SS) [ 26 ], transcription activator-like (TAL) effector [ 27 , 28 ], and Type II secretion system (T2SS) [ 23 ]. Receptors that interact with these effectors and the downstream signaling pathways eliciting specific responses remain to be identified.…”
Section: Bacterial-fungal Physical Interactionsmentioning
confidence: 99%
“…In the interaction between Rhizopus microsporus and Mycetohabitans rhizoxinica , fungal sporulation is contingent upon the successful establishment of symbiosis, which ensures maintenance of mutualism over generations [ 50 ]. Establishment of endofungal symbiosis between CaGg and G. margarita results in increased fungal sporulation [ 27 ]. In both cases, endobacteria are found in the spores, suggesting that control of host sporulation by endobacteria is sufficient to regulate their own transmission.…”
Section: Implications Of Bfis On Microbial Fitnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Components of this method include the transcription activator-like effector (TALE) DNA binding domain and DNA cleavage domain (FokI) (Barnett 2018) (Figure 2). TALEs are proteins secreted by the bacteria and help them to bind to sequences in the plant host genome (Richter, et al 2020). The DNA binder domain has repeated 33-35 amino acid sequences, in which the 12th and 13th amino acids are called the Repeat Variable Diresidue (RVD), are highly variable, and able to recognize a nucleotide (Malzahn and Qi 2021).…”
Section: Genome Editing Using Transcription Activator-like Effector N...mentioning
confidence: 99%
“…They compared different transfection methods (lipofectamine versus electroporation) and formats (plasmid DNA versus ribonucleoprotein) in delivering the CRISPR/Cas9 elements along with single-stranded oligodeoxynucleotides (ssODNs) to clinically relevant cells targeting major CFTR mutation loci. Their findings showed that among different combinations, electroporation of CRISPR/Cas9 and guide RNA (gRNA) ribonucleoprotein (Cas9 RNP) is the most effective strategy, leading to achieving a greater than 20% precise correction rate when it is applied to a patient-derived iPSC line carrying the dF508 mutation (Ruan, et al 2019). On the other hand, Smirnikhina et al (2020) tested P.F508del editing in cells from cystic fibrosis patients.…”
Section: Use Of Crispr/cas9 Gene Editing In the Treatment Of Cystic F...mentioning
confidence: 99%